INSL3 as a biomarker of Leydig cell functionality - Ivell, Richard; Wade, John D.; Anand-Ivell, Ravinder (Society for the Study of Reproduction, 2013)
Insulin-like factor 3 (INSL3) is a small peptide hormone made and secreted uniquely by mature Leydig cells in the testes of all mammals. Importantly, this expression and secretion appears to be constitutive and therefore reflects the differentiation status and number of the Leydig cells present, differing thereby from testosterone, which is acutely and homeostatically regulated by the hormones of the hypothalamic-pituitary-gonadal axis. As a consequence, the measurement of INSL3 either as mRNA in the testis or as secreted peptide circulating in the blood provides an excellent assessment of Leydig cell differentiation, for example, during fetal development, puberty, or aging or following exposure to endocrine-disrupting agents. Whereas INSL3 is proving increasingly useful as a biomarker for testis status, less is known about its functions, particularly in the adult male. Current evidence points to autocrine, paracrine, and endocrine roles, acting through the G-protein-coupled receptor called RXFP2, although more research is required to characterize these functions in detail.